PENGARUH TINGKAT PENDIDIKAN, PERTUMBUHAN EKONOMI, DAN JUMLAH PENDUDUK TERHADAP TINGKAT KEMISKINAN DI KABUPATEN HULU SUNGAI TENGAH - MUHAMMAD ALFIAN NOOR; SITI MUTMAINAH ZULFARIDATULYAQIN (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Poverty is a major problem in the economy. Therefore it needs to be studied to find solutions to reduce poverty in an area. This study aims to determine the effect of education level, economic growth and whether the population has a significant effect on poverty levels in Hulu Sungai Tengah Regency.This research was carried out in Hulu Sungai Tengah Regency using multiple linear regression with secondary data obtained from BPS South Kalimantan and BPS in Hulu Sungai Tengah Regency using time series data from 2001 to 2017. The data was analyzed using Eviews by looking at the magnitude of the coefficient of determination test (R2 test), simultaneous test (F test), and partial test (T test).Adjusted R2 which shows the effect of independent variables on the dependent variable has a strong effect of 79,42%. Probability F count of 0,000025 is smaller than 0,05 which means the estimated regression model is worth using for research. The results obtained from research conducted using the T test showed that the level of education and the number of inhabitants had a significant effect, but economic growth had no significant effect on poverty levels in the Hulu Sungai Tengah Regency.keywords: poverty level, education level, economic growth, and population